2017
DOI: 10.1016/j.cmi.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Amoxicillin dosing recommendations are very different in European countries: a cross-sectional survey

Abstract: National antibiotic stewardship programmes recommend monitoring antibiotic consumption and benchmarking. The WHO recommend the Anatomic Therapeutic Chemical classification and respective Defined Daily Doses (DDD) for drug utilization research [1]. This is the most frequently used unit of measure within the European Union (EU). Wide variations in antibiotic consumption exist between EU countries in the outpatient setting, ranging in 2012 from 11.3 (the Netherlands) to 31.9 DDD per 1000 inhabitants and per day (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 2 publications
(2 reference statements)
0
10
0
Order By: Relevance
“…This manuscript presents a detailed sub-group analysis of responses from all participating medical schools in France and Sweden, which were selected for further analyses for two reasons: first, there are significant differences between these countries in the intensity and type of antibiotic use [6, 7]. The consumption of antibiotics is about two times higher per capita in France based on Defined Daily Doses, (although dosing is lower in Sweden), and narrow-spectrum antibiotics are used more frequently in Sweden [8]. Second, the response rates in the study were broadly consistent for participating schools in both countries.…”
Section: Introductionmentioning
confidence: 99%
“…This manuscript presents a detailed sub-group analysis of responses from all participating medical schools in France and Sweden, which were selected for further analyses for two reasons: first, there are significant differences between these countries in the intensity and type of antibiotic use [6, 7]. The consumption of antibiotics is about two times higher per capita in France based on Defined Daily Doses, (although dosing is lower in Sweden), and narrow-spectrum antibiotics are used more frequently in Sweden [8]. Second, the response rates in the study were broadly consistent for participating schools in both countries.…”
Section: Introductionmentioning
confidence: 99%
“…In 2 of the 3 casereports, AICN contributing factors were found (low urinary pH, dehydration). One explanation of this discrepancy could be that France recommends higher intravenous AMX dose regimen in comparison to other European countries 38. Moreover, detection/identification of AMX crystals is not available in many countries, making the diagnosis of AICN difficult and probably leading to under-diagnosis.This study has several limitations.…”
mentioning
confidence: 99%
“…In a cross-sectional observational study of 653 French adults, Demor e et al observed that participants' self-reports were relatively reliable for recent use of an antibiotic, but not for its name; they therefore recommend the use of electronic medical records shared among prescribers [13]. In a European survey, ESGAP (ESCMID Study Group for Antimicrobial stewardshiP) authors questioned the validity of Defined Daily Doses for comparing antibiotic use between countries, as amoxicillin dosing recommendations vary hugely between countries [14]. Finally, Singh and Manchanda presented suggestions for high-impact interventions to control multidrug-resistant Gram-negative bacteria in resource-limited settings [15].…”
mentioning
confidence: 99%